The Short French Internet Addiction Test Adapted to Online Sexual Activities: Validation and Links With Online Sexual Preferences and Addiction Symptoms. Issue 6 (23rd July 2016) - Wéry, Aline; Burnay, Jonathan; Karila, Laurent; Billieux, Joël
Abstract : The goal of this study was to investigate the psychometric properties of a French version of the short Internet Addiction Test adapted to online sexual activities (s-IAT-sex). The French version of the s-IAT-sex was administered to a sample of 401 men. The participants also completed a questionnaire that screened for sexual addiction (PATHOS). The relationships of s-IAT-sex scores with time spent online for online sexual activities (OSAs) and the types of OSAs favored were also considered. Confirmatory analyses supported a two-factor model of s-IAT-sex, corresponding to the factorial structure found in earlier studies that used the short IAT. The first factor regroups loss of control and time management, whereas the second factor regroups craving and social problems. Internal consistency for each factor was evaluated with Cronbach's α coefficient, resulting in .87 for Factor 1, .76 for Factor 2, and .88 for the global scale. Concurrent validity was supported by relationships with symptoms of sexual addiction, types of OSAs practiced, and time spent online for OSAs. The prevalence of sexual addiction (measured by PATHOS) was 28.1% in the current sample of self-selected male OSA users. The French version of the s-IAT-sex presents good psychometric properties and constitutes a useful tool for researchers and practitioners.